Incidence of corn stunt disease in off-season corn hybrids in different sowing seasons - Costa, Rodrigo Véras da (2019)
The objective of this work was to evaluate the incidence of corn stunt disease and its effects on the grain yield of off-season corn (Zea mays) hybrids in different sowing seasons. The experiment was conducted in three sites in the state of Tocantins, in different sowing seasons, in a randomized complete block design, with 30 hybrids (treatments) and three replicates. Corn stunt disease incidence was assessed at 80 days after emergence, varying between hybrids and sowing seasons, with a marked effect of sowing season. The most resistant hybrids were: MG652 PW, Penta VIP, MG600 PW, NS90 PRO2, LG3040 VIP3, MG580 PW, and Defender VIP. The Fórmula VIP2 hybrid was the most susceptible to corn stunt disease. The incidence of the disease increased in the later sowing seasons, causing significant declines in grain yield. The most productive hybrids were: MG580 PW, SYN 5T78 VIP, 2B810 PRO, MG600 PW, Supremo VIP, 2B512 PW, NS92 PRO2, P30S31 VYH, MG652 PW, Penta VIP, SX5371 VIP3, and LG6036 PRO. Corn hybrids vary greatly in their resistance to corn stunt disease, and, the later the sowing season, the higher the disease incidence and the lower the grain yield.